Highly Tunable Selectivity for Syngas‐Derived Alkenes over Zinc and Sodium‐Modulated Fe5C2 Catalyst. Issue 34 (22nd July 2016) - Zhai, Peng; Xu, Cong; Gao, Rui; Liu, Xi; Li, Mengzhu; Li, Weizhen; Fu, Xinpu; Jia, Chunjiang; Xie, Jinglin; Zhao, Ming; Wang, Xiaoping; Li, Yong‐Wang; et al.
Abstract: Zn‐ and Na‐modulated Fe catalysts were fabricated by a simple coprecipitation/washing method. Zn greatly changed the size of iron species, serving as the structural promoter, while the existence of Na on the surface of the Fe catalyst alters the electronic structure, making the catalyst very active for CO activation. Most importantly, the electronic structure of the catalyst surface suppresses the hydrogenation of double bonds and promotes desorption of products, which renders the catalyst unexpectedly reactive toward alkenes—especially C5+ alkenes (with more than 50% selectivity in hydrocarbons)—while lowering the selectivity for undesired products. This study enriches C1 chemistry and the design of highly selective new catalysts for high‐value chemicals. Abstract : Direct synthesis of olefins using Fe‐based catalysts is a component of the traditional Fischer–Tropsch process. Na‐doping of Fe catalysts alters the surface electronic structure, which promotes CO activation and desorption of products, while suppressing hydrogenation of double bonds. A Na‐modulated catalyst is especially selective for alkenes (particularly C5+ ).